Operational Cost Requirements Analysis in Early Childhood Education - Yunita Murdiyaningrum; Novrian Satria Perdana (JPUD - Jurnal Pendidikan Usia Dini, 2020)
The government is attempting to obtain the access of Early Childhood Education pro- grams providing educational assistance. Unfortunately, the government has spent funds to calculate the unit costs that should not occur in the real world of education. In consequence, the aims of this study are to (1) calculate the amount of operational unit costs for Early Childhood Education pro- grams, and (2) enumerate variations and projections of the amount of the operational unit costs in Early Childhood Education programs by region category. This study uses quantitative data with pop- ulation of all Early Childhood Education institutions in Indonesia. The unit of analysis of this re- search is Early Childhood Education institutions consisting of kindergarten, Playgroup, Daycare, and ECCD units. The findings are that the highest operating unit cost is in TPA because there is a full day of service. Next is a Kindergarten institution because at this institution already has a special curriculum to prepare the child proceed to the level of basic education. Then the unit cost is the highest area in the eastern region. Recommendation in determining the amount of financial assistance it is necessary to consider the amount of operational unit costs so that the purpose of providing fi- nancial assistance is to improve access and quality can be achieved. Keywords: Early Childhood Education, Operational Unit Cost, Fund Aid Reference Afmansyah, T. H. (2019). Efektifitas Dan Efisiensi Pembiayaan Pendidikan. INA-Rxiv Paper. https://doi.org/10.31227/osf.io/5ysw4 Akdon. (2015). Manajemen Pembiayaan Pendidikan. Bandung: PT Remaja Rosdakarya. Aos, S., & Pennucci, A. (2013). K–12 CLASS SIZE REDUCTIONS AND STUDENT OUTCOMES: A REVIEW OF THE EVIDENCE AND BENEFIT–COST ANALYSIS. Washington State Institute for Public Policy, (13), 1–12. Azhari, U. L., & Kurniady, D. A. (2016). Manajemen Pembiayaan Pendidikan, Fasilitas Pembelajaran, Dan Mutu Sekolah. Jurnal Administrasi Pendidikan, 23(2). Belsky, J., Steinberg, L., & Draper, P. (1991). Childhood experience, interpersonal development, and reproductive strategy: An evolutionary theory of socialization. Child Development, 62(4), 647. Bijanto. (2018). Mengakreditasi PAUD dan PNF. Retrieved from https://banpaudpnf.kemdikbud.go.id/berita/mengakreditasi-paud-dan-pnf Brinkman, S. A., Hasan, A., Jung, H., Kinnell, A., Nakajima, N., & Pradhan, M. (2017). The role of preschool quality in promoting child development: evidence from rural Indonesia*. European Early Childhood Education Research Journal, 25(4), 483–505. https://doi.org/10.1080/1350293X.2017.1331062 Campbell-Barr, V. (2019). Interpretations of child centred practice in early childhood education and care. Compare, 49(2), 249–265. https://doi.org/10.1080/03057925.2017.1401452 Chandrawaty, Ndari, S. S., Mujtaba, I., & Ananto, M. C. (2019). Children’s Outdoor Activities and Parenting Style in Children’s Social Skill. Jurnal Pendidikan Usia Dini, 13(November), 217–231. https://doi.org/https://doi.org/10.21009/JPUD.132.02 Chrystiana, N., & Alip, M. (2014). Komponen Biaya Dan Biaya Satuan Operasi Pendidikan Taman Kanak-Kanak (Studi Kasus Di 3 Taman Kanak-Kanak). Jurnal Akuntabilitas Manajemen Pendidikan, 2(1), 70–80. https://doi.org/10.21831/amp.v2i1.2410 Denboba, A., Hasan, A., & Wodon, Q. (2015). Early Childhood Education and Development in Indonesia. In World Bank http://ideas.repec.org/b/wbk/wbpubs/22376.html Publications. Retrieved from Firdaus, N. M., & Ansori, A. (2019). Optimizing Management of Early Childhood Education in Community Empowerment. Journal of Nonformal Education, 5(1), 89–96. https://doi.org/10.15294/jne.v5i1.18532 Harris, D. N. (2009). Toward policy-relevant benchmarks for interpreting effect sizes: Combining effects with costs. Educational Evaluation and Policy Analysis, 31(1), 3–29. https://doi.org/10.3102/0162373708327524 Hasan, A., Jung, H., Kinnell, A., Maika, A., Nakajima, N., & Pradhan, M. (2019). Built to Last Sustainability of Early Childhood Education Services in Rural Indonesia. Retrieved from http://www.worldbank.org/prwp. Heckman, J. J., Moon, S. H., Pinto, R., Savelyev, P. A., & Yavitz, A. (2010). The rate of return to the HighScope Perry Preschool Program. Journal of Public Economics, 94(1–2), 114– 128. https://doi.org/10.1016/j.jpubeco.2009.11.001 Hollands, F., Bowden, A. B., Belfield, C., Levin, H. M., Cheng, H., Shand, R., ... Hanisch-Cerda, B. (2014). Cost-Effectiveness Analysis in Practice: Interventions to Improve High School Completion. Educational Evaluation and Policy Analysis, 36(3), 307–326. https://doi.org/10.3102/0162373713511850 Howard, S. J., & Melhuish, E. (2017). An Early Years Toolbox for Assessing Early Executive Function, Language, Self-Regulation, and Social Development: Validity, Reliability, and Preliminary Norms. Journal of Psychoeducational Assessment, 35(3), 255–275. https://doi.org/10.1177/0734282916633009 Institute of Medicine (Author), National Research Council (Author), Division of Behavioral and Social Sciences and Education (Author), and Families Board on Children, Youth (Author), C. on S. B.-C. M. for the E. of E. C. I. (Author). (2009). Strengthening Benefit-Cost Analysis for Early Childhood Interventions: Workshop Summary (A. Beatty, Ed.). Washington DC: National Academies Press. Keith, R. s. (2018). The Cost of Inequality: The Importance Of Investing In High Quality Early Childhood Education Programs (University of Colorado Springs; V ol. 53). https://doi.org/10.1017/CBO9781107415324.004 Lamy, C. E. (2014). American Children in Chronic Poverty: Complex Risks, Benefit-Cost Analyses, and Untangling the Knot. United Kingdom: Lexington Books; Reprint edition. Levin, by H. M., McEwan, P. J., Belfield, C. R., Bowden, A. B., & Shand, R. D. (2017). Economic Evaluation in Education: Cost-Effectiveness and Benefit-Cost Analysis (Third Edit). California: Sage Publication. Levin, H. (2001). Waiting for godot: Cost-effectiveness analysis in education. New Directions for Evaluation, 2001(90), 55–68. https://doi.org/10.1002/ev.12 Lovchinov, V. A., Mädge, H., & Christensen, A. N. (1984). On the thermodynamic properties of Vnx. In Materials Letters (Vol. 2). https://doi.org/10.1016/0167-577X(84)90080-6 Mujahidun. (2016). Pmerataan Pendidikan Anak Bangsa: Pendidikan Gratis Versus Kapitalisme Pendidikan. Tarbiyatuna, 7(1), 38–52. Nakajima, N., Hasan, A., Jung, H., Brinkman, S., Pradhan, M., & Angela Kinnel. (2016). Investing in school readiness : an analysis of the cost-effectiveness of early childhood education pathways in rural Indonesia. World Bank Research Working Paper, (September), 1–45. Retrieved from http://documents.worldbank.org/curated/en/656521474904442550/Investing-in-school- readiness-an-analysis-of-the-cost-effectiveness-of-early-childhood-education-pathways-in- rural-Indonesia Pidarta, M. (2013). Landasan Kependidikan Stimulus Ilmu Pendidikan Bercorak Indonesia. Jakarta: Rineka Cipta. SISDIKNAS, U. (2003). Undang-undang Sisdiknas No 20 Tahun 2003. (1). Suyadi, S. (2017). Perencanaan dan Asesmen Perkembangan Pada Anak Usia Dini. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 1(1), 65–74. Retrieved from http://ejournal.uin-suka.ac.id/tarbiyah/index.php/goldenage/article/view/1251 Tedjawati, J. M. (2013). Pendanaan Pendidikan Anak Usia Dini. Jurnal Pendidikan Dan Kebudayaan, 19(3), 346. https://doi.org/10.24832/jpnk.v19i3.294 UNESCO. (2013). Why every child deserves a quality education. 1–16. Retrieved from https://unesdoc.unesco.org/ark:/48223/pf0000223826 West, A., & Noden, P. (2019). ‘Nationalising’ and Transforming the Public Funding of Early Years Education (and care) in England 1996–2017. British Journal of Educational Studies, 67(2), 145–167. https://doi.org/10.1080/00071005.2018.1478058 West, A., Roberts, J., & Noden, P. (2010). Funding Early Years Education And Care: Can A Mixed Economy Of Providers Deliver Universal High Quality Provision? British Journal of Educational Studies, 58(2), 155–179. https://doi.org/10.1080/00071000903520850